Vakság és rövidlátás; Blindness and shortsightedness - Károly Fazekas (Hungarian Academy of Sciences, Institute of Economics, 2018)
– Institutions of the liberal democracies of the developed Western world are increasingly insufficient to deal with the ever worsening of social problems associated with technological progress, the rapid economic transformation of the economy, the demographic issues and the acceleration of demographic and migration processes. This essay reminds us that well-functioning institutions assume that citizens should have possess both cognitive and non-cognitive skills required by modern technology and organization. Economic analyzes on the subject show that non-cognitive skills in the developed countries' labor market are becoming more and more important. In many cases, the lack of non-cognitive skills is the very cause of the inefficiencies of local societies, the ever-increasing disturbance malfunctioning of institutions, and finally in some cases of the complete disintegration of local societies. At the same time these skills, however, can be improved and interventions at the early age of children provide the greatest yields. Although there are significant differences in the perception of the individual's freedom and responsibility between liberal and conservative social views, there is no difference between conservative and liberal opinions which do not diverge on the perspectives on the importance and social need of the enhancement of non-cognitive skills.
Keywords: I21; I26; I28; J24; R23; Z13; 330; non-cognitive skills; technological revolution; human capital investment; education policy; migration